2023
DOI: 10.3390/buildings13071675
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Evaluation of Indoor Environment, Occupant Satisfaction, and Energy Consumption in General Hospital in China

Abstract: Different functional areas within general hospitals have varying environmental requirements, with relatively high energy consumption. A comprehensive evaluation of the operational performance’s rationality is of great significance in hospitals’ energy conservation efforts. This study conducted an annual post-occupancy evaluation of a general hospital located in a hot summer and cold winter area in east of China. Two hundred and seventy-eight valid online satisfaction questionnaires, sixty valid point-to-point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…As a preliminary step in this direction, Bazzan et al [22] proposed an information management model that provides a structured database in which to store text-based resident complaints efficiently and effectively using artificial intelligence techniques. With respect to building maintenance management, a number of studies have taken the approach of examining occupant complaints and satisfaction as the basis for improving building performance strategies (e.g., heating, cooling, and elevators) and indoor environment quality in accordance with the results of interviews, text mining, and neural network analysis [9,16,[23][24][25]. In this respect, Roumi et al [26] developed a weight system involving indoor environment quality parameters for occupant satisfaction and energy efficiency based on survey results of surveys reflecting the opinions and experiences of the occupants.…”
Section: Literature Review 21 Related Work On Occupant Satisfaction A...mentioning
confidence: 99%
“…As a preliminary step in this direction, Bazzan et al [22] proposed an information management model that provides a structured database in which to store text-based resident complaints efficiently and effectively using artificial intelligence techniques. With respect to building maintenance management, a number of studies have taken the approach of examining occupant complaints and satisfaction as the basis for improving building performance strategies (e.g., heating, cooling, and elevators) and indoor environment quality in accordance with the results of interviews, text mining, and neural network analysis [9,16,[23][24][25]. In this respect, Roumi et al [26] developed a weight system involving indoor environment quality parameters for occupant satisfaction and energy efficiency based on survey results of surveys reflecting the opinions and experiences of the occupants.…”
Section: Literature Review 21 Related Work On Occupant Satisfaction A...mentioning
confidence: 99%
“…There are some studies [21][22][23][24] related to the influencing factors on building energy performance. Some studies have researched the energy consumption of office buildings [25], hospital buildings [26,27], commercial buildings [28], and hotel buildings [29][30][31][32]. The research mainly focuses on the impacts of energy consumption, the performance of energy consumption, the analysis and evaluation of energy consumption, and model and energy benchmarks for energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Medical centers have the highest energy consumption among the leading commercial buildings; their energy requirement is allocated to air conditioning, medical equipment, and maintenance [11]. Various studies have shown that 40% of consumption in medical centers comes from air conditioning systems [12].…”
Section: Introductionmentioning
confidence: 99%
“…Sun, Y. et al [11] carried out a comprehensive evaluation through satisfaction questionnaires of users for a medical center in China, improving energy efficiency. Seo et al [16] studied the impact of modifying the building envelope using green retrofits in South Korea.…”
Section: Introductionmentioning
confidence: 99%